Assessment and mitigation of ergonomics risk: An industrial practitioner case study of an electronic manufacturing production line / Lim Li Yin - Lim, Li Yin (2021)
Electronic manufacturing industry, especially in the final assembly area, involves a lot of repetitive movement, prolonged standing and awkward posture problems. Thus, this research has been carried out to determine the risk factors present in the existing workplace and to propose mitigation method to prevent or reduce the risk of Musculoskeletal Disorders (MSDs). The focus of this study is on the operators who working at the sound bar final assembly section. There are total of 15 operators being assessed. The operators are being observed and photos of their postures were taken. Rapid Upper Limb Assessment (RULA) was then carried out based on the photos taken. Those workstation where postures identified as high risk and medium risk were being redesigned using human simulation software (Siemens PLM Software, Jack 9.0). The redesigned workstation was being assessed using RULA and the risk score obtained was compared against the existing risk score to justify the effectiveness of the proposed mitigation method. Two stages of working posture assessment at an existing workstation and redesigned workstation have been carried out. At the existing workstation, out of the 19 postures, four are high risk (21%), five medium risks (26%), and ten are low risks (53%). Among the high risk, three are from the assembly area (75%), whereas the remaining one is from the packaging area (15%). Modifications of the workstation have been proposed to the existing workstation. Moreover, the comparison result of RULA analysis revealed that the redesigned workstation had promoted an effective solution to improve working posture. Based on the RULA analysis, those who were identified as medium and high risk were all reduced to low risk at the redesigned workstation.